Dissecting neurovascular coupling mechanisms: a role for adenosine A2A receptor: An Editorial highlight for 'Correlation of transient adenosine release and oxygen changes in the caudate‐putamen'. Issue 1 (15th December 2016) - Dale, Nicholas; Sebastião, Ana Maria
Abstract : Read the highlighted article'Correlation of transient adenosine release and oxygen changes in the caudate‐putamen' on page 13 . Abstract : This Editorial highlights a study by Wang and Venton in the current issue of the Journal of Neurochemistry. The authors present a simple hypothesis for the link between adenosine (Ado) release and the O2 transients. Neuronal activity causes adenosine production and release, which dilates blood vessels and gives a transient increase in oxygen delivery to tissue. Adenosine may act at two points in this scheme – on A2A receptors on the blood vessel to elicit dilation and on the neurons themselves to enhance the rate of adenosine transient production. Read the highlighted article'Correlation of transient adenosine release and oxygen changes in the caudate‐putamen' on page 13 .